ANALISIS PENANGKAPAN IKAN MENGGUNAKAN LACUDA DENGAN LAMPU LED SEBAGAI ALAT BANTU PENANGKAPAN IKAN PADA ALAT TANGKAP BAGAN TANCAP DI KABUPATEN BANGKA TENGAH - Kurniawan Kurniawan; Wahyu Adi; Eva Utami; Ari Anggara (Akuatik: Jurnal Sumberdaya Perairan, 2018)
Under water lamp (Lacuda) is one of the solutions to the problems of lift net fisherman who uses lights above the water level. Lacuda technology is less developed, fishermen have difficulty to make improvements, difficult to find stores selling Lacuda, and the price is still relatively expensive. LED lamps have better specifications when compared with incandescent lamps. This study aims to find out how to assemble lacuda using LED lights, analyzing the productivity of lift net using LED lacuda lights, knowing the characteristics (weakness of excess) lacuda LED light and its development strategy. The method used in this research is fishing or experimental fishing trials and data analysis using comparative descriptive analysis. The catch with Lacuda LED is 95.6 kg and the catch with fishing light is 73.7 kg. SR analysis showed a real effect between the type of lamp treatment with F count 5.0892 and F table 4.38 with 95% confidence level. Further test of DMRT showed that LED lacuda treatment gave the highest yield on fish catch in lift net . Characteristics of advantages and disadvantages lacuda LED operational cost-effective, providing more catch, easy to carry. Lacuda LEDs are prone to leakage, using multiple cables, simple dim systems